Applicability of Microcellular Injection Molding Process - Brdlík, Pavel; Rajnoha, Vojtěch (Manufacturing Technology Journal, 2019)
Microcellular injection molding is relatively new and progressive technology for production of lightweight constructions. The weight reduction, elimination of sink marks, internal stresses and deformation of products are the main advantages of this unconventional technology. On the other hand, decrease in mechanical properties and poor surface quality are the application restrictions. There are several aspects affecting formation of microcellular structure and final properties of injection molded products. As a one of the most important aspects there is used material. Therefore, the main goal of this article was investigation the influence of different types of thermoplastic materials on the microcellular structure formation and mechanical properties of products. Further, the influence of holding pressure on products quality was also evaluated.
Keywords: Microcellular Injection Molding; Thermoplastic Materials; Microcellular Structure; Mechanical Properties